CLOUD STORAGE SECURITY AND RELIABILITY: A STRUCTURAL EQUATION MODELING APPROACH AMONG IT PROFESSIONALS IN PAKISTAN’S TECH ECOSYSTEM - Anjum Ara,; Syed Ahmed Raza ,; Yasir Ali Mar,; Javed Ahmed Dahri, (Spectrum of Engineering Sciences, 2025)
In this study we try to find out IT professionals’ perceptions about cloud storage security and reliability within the domain of Pakistan’s tech ecosystem and specifically in Hyderabad city. The research on how perceived data backup habits, perceived risks, perceived reliability of a cloud storage provider, and perceived trust in that provider directly and indirectly affect the cloud storage adoption intentions is conducted using the Structural Equation Modeling approach. The data was collected from 144 IT professionals working in software houses, academic institutions and tech startups using a structured questionnaire. It is found that perceived risk and behaviors regarding data backup significantly reduce perceived reliability while the perceived trust significantly increases perceived reliability. Additionally, belief in reliability is strongly linked to intention to use cloud storage solutions. A mediation analysis is used to confirm that perceived reliability is a mediator of these relationships between trust and risk and adoption intention. These insights provide some valuable implications for cloud service providers and policymakers interested in encouraging adoption of cloud services so that they can address concerns on reliability and build user trust.